2010
DOI: 10.1159/000314685
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Exercise Effects on Attentional Control in Older Road Cyclists

Abstract: Background: Research on visual attention control of older road cyclists, who represent a subgroup of traffic participants, is still scarce and studies on their attentional performance while cycling are completely lacking. Objective: The present study assessed whether attention control performance of older individuals with a history of participation in road cycling is affected by concomitant cycling exercise. Acute exercise effects were also analyzed in co-aged aerobically trained and sedentary noncyclists to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 57 publications
(38 reference statements)
3
41
1
Order By: Relevance
“…The RVIP results may reflect this greater metacognitive awareness and attentional control. This is line with previous research as well observing that older expert orienteers, older cyclists, and older athletes having better attentional skills to modulate their attention and reaction time than nonathletes (Pesce, Cereatti, Casella, Baldari, & Capranica, 2007;Pesce, Cereatti, Forte, Crova, & Casella, 2011) and children participating in exercise interventions having increased meta-cognition as compared to their peers (Tomporowski, McCullick, Pendleton, & Pesce, 2015).…”
Section: Attentionsupporting
confidence: 93%
“…The RVIP results may reflect this greater metacognitive awareness and attentional control. This is line with previous research as well observing that older expert orienteers, older cyclists, and older athletes having better attentional skills to modulate their attention and reaction time than nonathletes (Pesce, Cereatti, Casella, Baldari, & Capranica, 2007;Pesce, Cereatti, Forte, Crova, & Casella, 2011) and children participating in exercise interventions having increased meta-cognition as compared to their peers (Tomporowski, McCullick, Pendleton, & Pesce, 2015).…”
Section: Attentionsupporting
confidence: 93%
“…However, given the results of the present study, where exercise had similar effects on behavioral performance in both EI groups, it appears that, regardless of whether moderate or high intensity, acute resistance exercise could be a viable approach to enhancing the executive functions involving inhibitory control and attention in young male adults. The improved behavioral performance with regard to central executive functioning found in this work could be related to increases in neural activation or general physiological arousal (Magnie et al, 2000; Joyce et al, 2009; Lambourne and Tomporowski, 2010; Dietrich and Audiffren, 2011; Pesce et al, 2011). …”
Section: Discussionmentioning
confidence: 73%
“…With regard to resistance exercise, a growing number of work has strongly supported the view that executive functioning performance is enhanced via chronic resistance exercise (Perrig-Chiello et al, 1998; Ozkaya et al, 2005; Cassilhas et al, 2007; Liu-Ambrose et al, 2010), but that such a facilitative effect, as measured by behavioral indices, can also be found via acute resistance exercise (Chang et al, 2012, 2014). However, while previous studies have implicated the physiological (e.g., arousal) or hormonal (e.g., neurotrophic factors) responses to acute exercise intervention as the basis of any improvements in behavioral performance following physical exercise (Magnie et al, 2000; Joyce et al, 2009; Lambourne and Tomporowski, 2010; Dietrich and Audiffren, 2011; McMorris et al, 2011; Pesce et al, 2011; Tsai et al, 2014), no research has yet been conducted to explore the potential mechanisms underlying this process using electrophysiological and biochemical markers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, performance on executive tasks shows greater age-related reductions compared with non-executive tasks. 31,41 Previous studies have shown evidence that acute exercise has beneficial effects on executive function in older adults 8,15,42 and middle-aged adults. 43e45 More importantly, a meta-analytic review demonstrated that individuals with lower cognitive status, such as older adults and clinical populations, have larger positive effect sizes than the normal population, which implies that individuals with lower cognitive abilities may benefit from acute exercise to a larger extent.…”
Section: Exercise Manipulation Checkmentioning
confidence: 99%